Dicionário enciclopédico de topônimos do estado de Mato Grosso do Sul: uma proposta de modelo - Castiglioni, Ana Claudia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research has broader objective to elaborate a propose of format of toponymic encyclopedic dictionary and for that we use as corpus the repertoire of the lexical units that designate the names of the geographical features related to water, i.e. hydronym. The hydronyms that are part of our research refer to elements hydrographic stream, bay, marsh, head, cape, waterfall, canal, cataracts, corixão, corixo, stream, estuary, lake, pond, spring, dam, creek, river, stream river, little river, jump, sanga, ebb back. These hydronyms were obtained at database toponymic of the State of Mato Grosso do Sul project – ATEMS. To achieve the main objective of our research we reflect on the status of the map as text source toponymic research and how in it is recorded the toponymic syntagma; we analyze some Brazilian toponymic dictionaries already published to understand how they work and what the goals of a work like this; we organize a conceptual system of hydronym of Mato Grosso do Sul based on theoretical support of Terminology considering the hierarchical and non-hierarchical relationships between the lexical units that are part of our corpus; we propose three microstructure models of headwords: two main, one for headwords whose entries describe concepts related to hydrographic elements and key concepts of terminology and another set for the establishment of the headword that have as inputs the toponymic syntagmas, and a third remitting; we organize a system of reference foreseeing the presence of the variant toponymic syntagmas and indicating to person who is consulting the dictionary which headword he/she should look for to find the information who wants. Finally, we organize a sampling of entries as demonstration of what it could come to be the dictionary. We develop these actions to reach the main goal of presenting a proposal of model of dictionary to toponymic syntagmas, as regards the superstructure, the macrostructure and microstructure ...

Esta pesquisa tem como objetivo mais amplo elaborar uma proposta de formato de dicionário enciclopédico toponímico e, para isso, utilizamos como corpus o repertório das unidades léxicas que designam o nome dos elementos geográficos referentes à água, ou seja, os hidrônimos. Os hidrônimos que fazem parte de nossa pesquisa se referem aos elementos hidrográficos arroio, baía, cabeceira, cabo, cachoeira, canal, catarata, corixão, corixo, córrego, foz, lago, lagoa, nascente, represa, riacho, ribeira, ribeirão, rio, riozinho, salto, sanga, vazante, volta. Esses hidrônimos foram obtidos no banco de dados do projeto Atlas Toponímico do Estado de Mato Grosso do Sul – ATEMS. Para alcançar o objetivo principal da nossa pesquisa refletimos sobre o estatuto do mapa como texto fonte de pesquisa toponímica e como nele estão registrados os sintagmas toponímicos; analisamos alguns dicionários toponímicos brasileiros publicados para entender como funcionam e quais os objetivos de obras como essas; organizamos um sistema conceptual dos hidrônimos de Mato Grosso do Sul com base no amparo teórico da Terminologia, considerando as relações hierárquicas e não hierárquicas existentes entre as unidades léxicas que fazem parte de nosso corpus; propomos três modelos de microestrutura de verbetes: dois principais, um para verbetes cujas entradas designam conceitos relativos a elementos hidrográficos e a conceitos-chave do conjunto terminológico, outra para a constituição dos verbetes que têm como entradas os sintagmas toponímicos e uma terceira remissiva; organizamos um sistema de remissivas prevendo a presença de sintagmas toponímicos variantes e indicando ao consulente qual verbete deve procurar para encontrar a informação que deseja. Por fim, organizamos uma amostragem de verbetes como demonstrativo do que poderá vir a ser o dicionário. Desenvolvemos essas ações para chegar ao objetivo principal de apresentar uma proposta ...
Keywords: Lingüística aplicada; Análise linguística; Toponímia; Mato Grosso do Sul - Hidrônimos; Linguistic analysis (Linguistics)